Files associated with: "Investigations of electrophysiological mechanisms related to myocardial ischaemia in hypertrophic cardiomyopathy: implications for arrhythmic risk, ECG diagnosis, and antiarrhythmic therapy" - Coleman, J (University of Oxford, 2024)
Contains meshes, MonoAlg3D source files and config files required to reproduce investigations in the DPhil thesis "Investigations of electrophysiological mechanisms related to myocardial ischaemia in hypertrophic cardiomyopathy: implications for arrhythmic risk, ECG diagnosis, and antiarrhythmic therapy".